A two-dimensional distributed activation energy model for pyrolysis of solid fuels. (1st September 2021) - Ma, Junfang; Liu, Jiaxun; Jiang, Xiumin; Zhang, Hai
Abstract: Pyrolysis kinetic models are pivotal for understanding and optimizing the gasification, distillation, and combustion processes. This paper proposes a novel two-dimensional distributed activation energy model (2D-DAEM), which is achieved via extending the classical DAEM to the 2D plane of activation energy E and pre-exponential factor A . The performance of the proposed model was evaluated based upon comprehensive analyses of complex reactions such as co-pyrolysis. The results show that the 2D-DAEM outperforms the classical DAEM in terms of efficiency and accuracy. Specifically, the co-pyrolysis analysis of pine woodchips (PINE) and polyethylene terephthalate (PET), shows that the classical DAEM tends to underestimate the ln A values (i.e., 43.0 for PINE pyrolysis; 42.0 for PET pyrolysis; but 39.2 for PINE&PET co-pyrolysis), while the ln A value of 2D-DAEM (about 43.0 for all) is more reasonable. Additionally, the 2D-DAEM is employed to study the influence of coal particle size on pyrolysis. It is observed that the 25 μm coal has the highest reaction rate under both 500 K and 1500 K iso-thermal processes. As a more normative, reasonable, and accurate model, the proposed 2D-DAEM is bound to enhance the practice of reaction prediction, material analysis, and process design. Graphical abstract: Image 1 Highlights: A two-dimensional distributed activation energy model was developed. The performance of the proposed model was comprehensively evaluated based upon pyrolysis of different fuels. The 2D-DAEM eliminates the deviation in the high temperature region of the classical DAEM. The 2D-DAEM avoids the ln A underestimation of the classical DAEM. 25 μm is selected as the optimal particle size for maximum pyrolysis rate.